Fluorescence Spectra of Salt Solutions of Coumarin Crown Ethers - Bulut, Mustafa; Göçmen, Ayten; Erk, Clakil; AKYÜZ, SEVİM (Taylor and Francis Online, 1995)
The fluorescence spectra of the coumarin derivatives of crown ethers obtained from 7,8-dihydroxycoumarins were studied in the presence of some alkali and alkaline earth cations in acetonitrile. The altered fluorescence spectra were examined qualitatively from the point of enhancement of fluorescent quantum yields as well as a resonance. Heavy metal effects were eliminated since there is no influence of the metal salts on the spectra of the initial coumarin derivatives. However, both the complexation-enhanced fluorescence and complexation-enhanced quenching spectra is observed in the fluorescence emission and excitation spectra of macrocyclic ether-coumarin / metal salt systems. The origin of results are briefly discussed in terms of crown ether complexation. In water solutions almost no such effects were observed.
Keywords: Macrocyclics; coumarin-crown ethers; cation complexation; fluorescence spectra